Combining paid work and eldercare. Labour market support for informal carers of older people in international comparisons - Furmańska-Maruszak, Agnieszka Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper aims at analysing the ways of supporting informal carers in achieving and maintaining the balance between paid work and eldercare in Poland and selected EU countries. The possibility to achieve balance between work and care depends on the availability of formal eldercare. The better access to formal care the less probable the imbalance between paid work and eldercare is. Moreover, the paper aims at analysing the eagerness of informal careres to take up part-time job as a way of achieving work-care balance. There are also examples of employment legislation recognizing carers examined in Poland and selected EU countries.